KEPEDULIAN DAN KESADARAN KONSUMEN MENGONSUMSI PRODUK SAYUR/BUAH ORGANIK DI PASAR MODERN, SURABAYA - Syah, Mirza Andrian; Sari, Putri Nurmalita; Azizah, Bena (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2025)
In today’s modern era, public awareness of healthy living is steadily increasing. One of the key aspects of maintaining health is the consumption of fruits and vegetables, which serve as vital sources of essential nutrients. The growing demand reflects an increasing societal awareness of the importance of incorporating fruits and vegetables into a healthy diet. However, consumers' purchasing decisions regarding organic products are influenced by specific factors. This study aims to analyze the level of consumer awareness and the determinants influencing the purchase decisions of organic fruits and vegetables in modern markets across Surabaya City. Data were collected from 385 respondents using accidental sampling at eight modern markets. Consumer awareness was measured using a Likert Scale based on five key indicators: knowledge, attitude, consumption behavior, willingness to pay, and accessibility. Factor analysis was conducted using PLS-SEM. The results show that 39.74% of respondents had a very high level of awareness and 60.26% had a high level of awareness regarding organic products, particularly among individuals aged over 55 and those with an income above IDR 6,000,000. This awareness is reflected in consumers’ understanding of the health and environmental benefits of organic products. Path analysis revealed that personal preference, health knowledge, price, availability, income, and location significantly influenced purchasing decisions. In contrast, product quality and taste were not significant, likely due to the limited variety of organic products available in modern markets. These findings highlight the dominance of practical and contextual factors in purchasing decisions, indicating that accessibility and affordability play a more decisive role than intrinsic product attributes in markets with limited options. Keyword: Consumer Awareness; Fruit; Vegetable; Organic; Modern Market.